In vitro Comparative Studies of the Leaf Extracts of Four Different Types of Calamus Species - Sultana, Munsifa; Das, Sajan; Shahriar, Mohammad; Akhter, Rumana; Mohamed, Isa Naina; Bhuiyan, Mohiuddin Ahmed (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The leaf extracts of Calamus tenius, Calamus viminalis, Calamus guruba and Calamus erectus possessed various phytochemicals including alkaloids, carbohydrates, saponins, phenols, tannins, flavonoids, glycosides, fixed oils and steroids. The point of the present investigation was to compare the antioxidant profile of different leaf extracts of these species. In the present study, methanol, ethanol and chloroform extract of leaf of C. tenius, C. viminalis, C. guruba and C. erectus were explored for in-vitro thrombolytic activity, membrane stabilizing activity by using hypotonic solution-induced & heat-induced hemolysis and antioxidant profile. Ethanol extracts of all plant species demonstrated the highest percentage of clot lysis. During hypotonic solution-induced hemolysis, methanol extract of C. erectus inhibited 59.74% whereas during heat induced condition ethanol extracts of all plant species demonstrated the highest percentage inhibition of hemolysis of RBCs. The screenings of the plants revealed that leaf extracts contain phenolic and flavonoid contents in great amount with the high level of antioxidant capacity. The chloroform extract of C. tenius (2.45 μg/ml) and methanol extract of C. erectus (1.74 μg/ml) leaf showed potent DPPH and H2O2 scavenging activity, respectively. The nitric oxide scavenging activity was not significantly different for methanol, ethanol and chloroform extracts. Methanol, ethanol and chloroform extracts of these four plants showed medium to moderate reducing power and cupric reducing capacity in comparison to standard. A strong relationship was found between the antioxidant activity of the extracts with their total phenolic and flavonoid contents. Dhaka Univ. J. Pharm. Sci. 21(2): 173-181, 2022 (December)